A review – plant essential oils active against Helicobacter pylori. Issue 3 (4th May 2022) - El-Sherbiny, Gamal M.; Elbestawy, Mahmoud K. M.
ABSTRACT: Helicobacter pylori ( H. pylori ) is an important pathogen in the gastrointestinal which colonizes the mucoid layer of the stomach in approximately 50% of humans worldwide. It is closely associated with chronic gastritis, peptic ulcers, and gastric cancer. Current research and clinical challenge are the increased rate of H. pylori resistance to antibiotics. For this reason, the search for an alternative and effective new therapeutic scheme is important and urgent. The aim of this review is to highlight plants' essential oils that exhibit potential anti- H. pylori activity. Electronic databases, NCBI-PubMed, and Science Direct were explored for plant essential oils with anti- H. pylori properties using keywords plant essential oils against H. pylori, virulence factor.